Human anatomy - Martini Frederic H (USA Pearson education, 2009)
The study of the human anatomy and anatomy-related topics. Contains photographs organized in an interactive format consisting of thirteen modules.
Title from disc label.
Production level cataloging.
System requirements for Windows: IBM-compatible PC; Windows 95, 98, ME, NT, 2000, XP.
System requirements for Macintosh: Power PC (OS 8.6 or later), OS X (OS 10.1 or later).
Keywords: Human anatomy -- Software